ED Referral Dramatically Reduces Delays of Initial Evaluation in a French TIA Clinic - Raposo, Nicolas; Albucher, Jean François; Rousseau, Vanessa; Acket, Blandine; Chollet, François; Olivot, Jean Marc (Frontiers in Neurology, 2018)
Background: The risk of recurrent brain infarction (BI) is high within the first hours after a transient ischemic attack (TIA). Emergent, specialized, and tailored patient management in a TIA program reduces the risk of recurrent BI after TIA by 80%. New antithrombotic strategies have been successfully tested within 12 hours after TIA onset. We aim to investigate the factors associated with a delay of more than 12 hours from TIA onset to evaluation in our TIA clinic. Methods: In consecutive patients evaluated in our TIA clinic from 01/2012 to 11/2013, we prospectively collected delays from onset to arrival, baseline characteristics, discharge diagnosis and recurrent BI at 1 week. Referring pathways were dichotomized between office-based physicians (OBP) and emergency departments (ED). Univariate and multivariate logistic regression were performed. Results: 354 patients were evaluated. Mean (+/- SD) age was 61 years (+/-18). Median (IQR) ABCD2 score was 3 (2-4). Median (IQR) delay from onset to evaluation was 8 hours (4-48). Overall, 185 (52%) were referred by OBP vs. 169 (48%) by ED. Evaluation was initiated within 12 hours among 201 (57%) patients. After logistic regression, OBP referral was by comparison with ED the only independent factor associated with an evaluation delay > 12 hours (OR 5.7, 95% CI: 3.5-9.3, p<0.0001). Conclusion Our results suggest that preliminary assessment by OBP may increase the delay to initiate the emergent evaluation of TIA patients. Promoting direct admission to TIA clinics through ED may be an efficient alternative for high risk TIAs.